Studies on Growth, Productivity and Economics of Potato as Influenced by Nutrient Management in Potato-sesame Cropping Sequence under Red and Lateritic Soil - Chowdhury, Soumita; Barik, Arun Kumar; Patre, Siddharth Shankar; Kumar, Basant (International Journal of Bio-resource and Stress Management, 2024)
A field experiment was carried out at agricultural farm of the Institute of agriculture,Sriniketan Birbhum, West Bengal, India during winter months (November to February) of 2021–2022 and 2022–2023 to study growth, productivity and economics of potato as influenced by nutrient management in potato-sesame cropping sequences under red and lateritic soil. The experiment was laid out in randomized block design having nine treatments with each treatment replicated thrice. Growth attributes, yield components, yield and economics of potato were influenced significantly by nutrient management in potato-sesame cropping sequences on pooled data basis. Among different nutrient management practices in potato-sesame cropping sequences, highest growth and yield attributes of potato was achieved from treatment having 100% NPK in potato+100% NPK in sesame in potato-sesame sequence. This was statistically at par with 100% NPK in potato+75% NPK in sesame+crop residues of potato and 100% NPK in potato+75% NPK in sesame. Higher tuber yield (23.7 t ha-1), haulm yield (1.4 t ha-1), gross return (` 283.78×103 ha-1), net return (` 189.49×103 ha-1) and return rupee-1 investment (` 3.0) was fetched from 100% NPK in potato+100% NPK in sesame which was at par with 100% NPK in potato+75% NPK in sesame+crop residues of potato. So, use of 100% NPK in potato+75% NPK in sesame+crop residues of potato was promising in terms of productivity and profitability of potato in potato-sesame cropping sequence by reducing 25% NPK fertilizers in potato-sesame cropping sequence.